The name game: Is there a reputation bias in figure skating judging? - Findlay, Leanne C. (University of Ottawa (Canada), 2001)
Expectations for performance, such as an expectation set by within team order in gymnastics (Scheer & Ansorge, 1975; 1980), have been shown to create a non-performance bias in terms of sport performance evaluation. Plessner (1999) found such a bias to influence both the encoding and evaluation phases of gymnastics judgement. In the sport of figure skating, the encoding phase is considered the period during which a judge perceives elements and any errors that may occur. After the performance is complete, judges evaluate the merit of the performance by providing two marks that are combined to create an ordinal rank, which is considered the evaluation phase of judging. The current study investigated whether or not expectations created by the reputation, or name, of an athlete occurs in the sport of figure skating, and if so, in what phase of the process, encoding or evaluation. Fourteen female figure skaters' short programs were viewed by judges to whom the athletes were either known or unknown. Judges were asked to provide technical base marks, technical merit, and artistic impression marks (all indicative of the evaluation phase), as well as to identify the elements and associated deductions (the encoding phase variables). Post-experiment, the ordinal placements of the skaters were calculated and used to define whether biases do exist at a basic level. Indeed, the skaters' average ordinal placement was higher when they were known by the judge as compared to unknown (t = 2.43, p < .05). A more in-depth analysis revealed that skaters received higher technical merit and artistic impression marks, as well as technical base marks when known to the judges. No significant differences, however, were found for deductions allocated for errors or for the judges' percent correctness in perceiving the elements performed. Thus, the findings suggest that a reputation bias exists at the level of the evaluation phase, but not during the encoding phase, of figure skating judging.
Keywords: Psychology, Cognitive.